2018
DOI: 10.1021/acs.cgd.7b01121
|View full text |Cite
|
Sign up to set email alerts
|

Solvates of Zwitterionic Rifampicin: Recurring Packing Motifs via Nonspecific Interactions

Abstract: Antibiotic rifampicin was recrystallized from solutions containing aliphatic alcohols, ketones, or dimethyl sulfoxide. Thirteen new solvates were obtained that were studied by X-ray crystallography. In these solvates rifampicin exists in a zwitterionic form. The reported solvates are classified into eight different structural types. Whereas rifampicin molecules in the solvates form diverse assemblies via hydrogen bonds, the recurring structural motif in these crystals is generated by nonspecific intermolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The analysis of these spectra introduces a new and important factor, namely, a water (35) groups are present, albeit, exclusively in the solid state. 29 The X-ray structure of the zwitterionic RMP solvate with MeOH (Figure 4b) reported here, which is unique relative to the earlier reported ones, 30,31 points to an alternative way of possible stabilization of the ansa-bridge conformations by water. In this structure, the hydroxyl group of MeOH is included in the collective system of H-bonds that starts at NH(lactam) and ends at the acetyl carbonyl, however, at the expense of N( 2 S1 and S2).…”
Section: ■ Results and Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The analysis of these spectra introduces a new and important factor, namely, a water (35) groups are present, albeit, exclusively in the solid state. 29 The X-ray structure of the zwitterionic RMP solvate with MeOH (Figure 4b) reported here, which is unique relative to the earlier reported ones, 30,31 points to an alternative way of possible stabilization of the ansa-bridge conformations by water. In this structure, the hydroxyl group of MeOH is included in the collective system of H-bonds that starts at NH(lactam) and ends at the acetyl carbonyl, however, at the expense of N( 2 S1 and S2).…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…Bacchi et al showed earlier that water molecules stabilize the s -cis conformation of the diene fragment for nonionic rifamycin S (lacking C(3) substituent), where some cooperative interactions between O(1)­H, (O21)­H, O(23)­H, and OC(35) groups are present, albeit, exclusively in the solid state . The X-ray structure of the zwitterionic RMP solvate with MeOH (Figure b) reported here, which is unique relative to the earlier reported ones, , points to an alternative way of possible stabilization of the ansa -bridge conformations by water. In this structure, the hydroxyl group of MeOH is included in the collective system of H-bonds that starts at NH­(lactam) and ends at the acetyl carbonyl, however, at the expense of N(2)–H···N(38) intramolecular stabilization.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, because RIF is zwitterionic, it would act as anion at pH 9 leading to higher ionization and subsequent enhancement in water uptake. The observed elevation in EWC% at pH 9 in all tested films is due to the ionization of the hydroxyl group in p-HEMA that leads to enhance water uptake and entrapment 49 , 50 . The protonation of the primary alcohol groups in p-HEMA would result in ionic repulsion leading to expansion and increasing the probabilities of interaction with water.…”
Section: Discussionmentioning
confidence: 90%
“…[ 22 ] also studied the role of hydrogen bonds playing in the molecular self‐assembly process of sulfamethazine (SFZ) solvates and found that it was the mainly hydrogen bond that causes the self‐assembly of all four kinds of SFZ solvates. Although molecular stacking mode is also considered to be a factor that influences the stability of the solvates, [ 23–25 ] compared with the intermolecular interaction, research on the effect of stacking on the stability of solvates is still insufficient, and the study of the stacking mode could help us to further understand the stability of solvates.…”
Section: Introductionmentioning
confidence: 99%